PROFIL PENGETAHUAN HAKIKAT SAINS CALON GURU PENDIDIKAN BIOLOGI DI UNIVERSITAS BORNEO TARAKAN - Ribka Ribka; Vlorensius Vlorensius; Endik Deni Nugroho (Biopedagogia, 2020)
The purpose of this study was to determine the understanding of biology teacher candidates at the University of Borneo Tarakan regarding the nature of science. This type of research is a qualitative descriptive study. The instruments used were test questions and questionnaire sheets. The results of the research on understanding the nature of science for 121 biology teacher candidates at the University of Borneo Tarakan showed that the understanding of the nature of science for biology teacher candidates was categorized as good. The highest score for understanding the nature of science by prospective teachers on the aspect of creativity is 78, while the lowest score for understanding the nature of science by prospective teachers on the aspects of tentative and socio-cultural embeddednes is 65. Keywords:  nature of science, biology teacher candidates